Association between fat and fiber intake and cholesterol levels in patients with coronary heart disease: A cross-sectional study in Southeast Sulawesi, Indonesia - Suwarni, Suwarni; Wiralis, Wiralis; Anggar Sari, GP. Ghita (YCAB Publisher & IAKMI SULTRA, 2023)
Background: The prevalence of coronary heart disease continues to increase globally, and it is important to understand the factors associated with it. Objective: This study aimed to explore the association between fat and fiber intake with cholesterol levels in patients with coronary heart disease at the Outpatient BLUD Bahteramas General Hospital, Southeast Sulawesi Province, Indonesia. Methods: A cross-sectional study design was employed in this study. Data were collected from 55 patients with coronary heart disease using a semi-quantitative food frequency questionnaire and laboratory data on total cholesterol and HDL levels. Results: There was no significant association between fat and fiber intake with cholesterol level (p >0.05). Conclusion: No significant association was found between fat and fiber intake with cholesterol levels in patients with coronary heart disease. However, other factors may be contributing to the high cholesterol among these patients. Thus, future research is needed and considers using larger sample sizes to confirm the results. In the meantime, it is crucial to continue providing nutrition consultations that emphasize the importance of a balanced diet for patients with coronary heart disease.